MENENTUKAN MENENTUKAN PH TANAH DI LAHAN PESISIR PANTAI CERIMIN KABUPATEN SERDANG BERDAGAI - Rahmat Dwi Prasetyo (PUCUK : Jurnal Ilmu Tanaman, 2025)
Coastal land has an important role in supporting agricultural and fisheries activities, but often faces less than ideal soil, one of which is soil (pH). This study aims to identify the characteristics of soil pH in coastal land in Pantai Cermin District, Serdang Bedagai Regency, North Sumatra, as sustainable land management. Sampling was carried out at several different points in the coastal area with a depth of 0–20 cm and a depth of 20-40 cm, then analyzed in the laboratory using a 1:1, 1:2.5 and 1N KCl ratio of 2.5 and electrometry to determine the pH value. The results of the study according to location have a soil pH ranging from acidic (pH 4.3 – 6.1), which is caused by the influence of natural processes such as climate, biology, sea air, and high organic matter content. Several points according to indications of active acid sulfate soil that has the potential to decline if not managed with land productivity, Knowledge of pH characteristics is important as an initial step in selecting appropriate commodities, as well as for the application of improvements such as lime. In conclusion, information on soil pH in the coastal area of ​​Pantai Cermin is crucial in supporting environmental management in local agricultural productivity.